Migration attractiveness of the coastal zone of Russia's North-West: local gradients - Sokolova, Flera K.; Lyalina, Anna V. (Baltic Region, 2022)
A well-acknowledged driver of change, population movement intensifies the development of coastal territories. The Russian North-West holds a vast coastal zone. Granting access to the Baltic, the White, and the Barents Seas, it is an area of geostrategic importance where much of the country’s coastal economy - one of the national priorities - is located. Push and pull factors are enormously diverse in the area, as are migration flows forming attraction poles for migrants. There is little research on the issue despite its social and practical significance. Thus, research is required to examine how the coastal factor can benefit the migration attractiveness and human resources of Russian coastal territories of geostrategic importance. This study aims to delineate coastal territories and investigate local migration flows compared to those recorded in inland regions. The research draws on the concept of coastalisation, employing universal, geographical, and statistical research methods. It uses documentary sources and official 2011ö--2020 statistics. The findings show that the coastal position and maritime economic activity are relevant factors for migration attractiveness. Saint Petersburg and the coastal municipalities of the Leningrad and Kaliningrad regions are more attractive to migrants than more northerly territories. However, there are attraction poles farther north too, and the coastal zone of the Arkhangelsk region attracts more migrants than its inland part. The study demonstrates the growing polarisation of migration space in the coastal areas and especially agglomerations. Changes in the age structure of immigration flows have caused social factors in attractiveness to migrants to replace employment-related factors.